Linking microstructure and processing defects to mechanical properties of selectively laser melted AlSi10Mg alloy. (December 2018) - Larrosa, N.O.; Wang, W.; Read, N.; Loretto, M.H.; Evans, C.; Carr, J.; Tradowsky, U.; Attallah, M.M.; Withers, P.J.
Highlights: Microstructure and processing defects in SLM AlSi10Mg were investigated. As-Fabricated, T6 and HIPped samples were studied. Microstructiral changes, densification and mechanical behaviour has been evaluated. T6 treatment led to a drop in tensile strength. HIPping led to reduced tensile strength and improved tensile elongation-to-failure. Higher strength in the AF samples was attributed to the cell-like structures. Pancake shaped pores act as fatigue crack initiation and propagation sites. Abstract: Here we analyse the relationship between the monotonic and cyclic behaviour of cylindrical AlSi10Mg (CL31 AL) samples fabricated by Selective Laser Melting (SLM) to the build direction, the presence of manufacturing defects (pores, voids, oxides, etc.) and the beneficial effect of post-processing – T6 and hot isostatic pressing (HIP) – treatments. Correlative Computed Tomography (X-ray tomography, optical microscopy, electron backscatter diffraction, SEM and TEM) is used to characterise the microstructure and the three-dimensional (3D) structure of fatigue samples to shed light on the role of defects on the experimental fatigue behaviour. Pancake-shaped pores are observed in the plane of the deposited layers having a 130% higher volume fraction for the vertical layering deposition (VL) than for horizontal layered (HL) orientations and being larger and flatter. Further, while T6 treatment had relatively little effect on reducing porosity, the HIPping reduced the pore fraction by 44% and 65% for VL and HL samples, respectively. T6 + Hipping decreased the yield stress and the ultimate tensile strength considerably while increasing elongation and reduction of area accordingly. Our results suggest that the fatigue life seems to be dominated by the presence of these crack-like (pancake-like) defects perpendicular to the loading direction such that it is better to build samples transverse to the highest fatigue loads. T6 heat treatment appears to reduce the fatigue strength of the material regardless of the AM deposition scheme due to two main reasons: (i) a reduced tensile strength of the T6-treated alloy and (ii) the inability to reduce (or even increasing) porosity in both layering orientations. The presence of larger and flatter pores/voids (crack-like defects) after T6 were observed. From X-ray tomography, it was observed that T6 + Hipping resulted in improved densification and in smaller and blunter defects which resulted in improved fatigue lives.